Fe(Ⅱ) improving sulfurized Anammox coupled with autotrophic denitrification performance: Based on interspecies and intracellular electron transfer. (November 2022) - Lin, Wenmin; Liu, Huimin; Zhang, Yujie; Chen, Yuancai; Qin, Yexia
Graphical abstract: Highlights: Core-shell S 0 @AnAOB + SOB sludge accelerated the mass and electron transfer. Q pool and NAR activities were improved to ensure the stable nitrite supply. High HDH activity enhanced the nitrogen metabolism. Fe(Ⅱ) accelerated electron hopping and INET by increasing redox species secretion. Abstract: Insufficient nitrite supply and slow metabolism of Anammox bacteria (AnAOB) impeded the application of Anammox process in low level ammonia (LLA) (≤50 mg/L) wastewater. At the initial concentration of 50 mg/L NH4 + -N and 75 mg/L NO3 – -N, Fe(Ⅱ) (10 mg/L) promoted the total nitrogen removal efficiency from 80.79 to 94.92 % by core–shell sulfurized AnAOB coupled with sulfur oxidizing bacteria (S 0 @AnAOB + SOB). AnAOB outcompeted SOB for nitrite, because the addition of Fe(Ⅱ) not only increased the nitrate reductase activity (37.54 %), but also enhanced the metabolism and electron capture ability of AnAOB, which was highly related with energy metabolic process: hydrazine dehydrogenase activity increased to 139.00 %. Particularly, Fe(Ⅱ) accelerated the interspecies electron transfer (INET) (from SOB to AnAOB) by stimulating the secretion of redox species and electron hopping in EPS. This study shed light on the mechanism of Fe(Ⅱ) promoting electron transfer in S 0 @AnAOB + SOB system, and provided basis for engineering practice.